Cara Pandang Barnabas si Anak Penghiburan - Susanto, Ferry (P3TK, Sanata Dharma University, 2019)
This paper deals with a narrative analysis on a figure, named Barnabas in the Book of Acts of The Apostle. The story of Barnabas in the Bible cannot be separated with Paul, the famous character in the Early Church, who is known as the Apostle of the nations. Transformation of Barnabas in Acts displays a role model for every Christians until today. Luke in Acts 9 tells the beginning of relationship between Barnabas and Saul, where Barnabas helped Saul from the series of rejections from the disciples of the Lord in Jerusalem. This relationship perfectly developed until they served hand in hand to spread the good news to the nations. As known, Barnabas and Saul have a serious conflict about Mark, the young man, the nephew of Barnabas. Eventually, this dynamic duo of the Early Church separated, where they took their own paths (Acts 15:39). Despite they have a disagreement, there is no hostility between them. From the story of Barnabas, we can learn how to solve so many differences in our missions as the disciples of Jesus.